Amplitude modulation coding in awake mice and squirrel monkeys - Hoglen, Nerissa E G; Larimer, Phillip; Phillips, Elizabeth A K; Malone, Brian J; Hasenstaub, Andrea R (Journal of neurophysiology, 2018)
Both mice and primates are used to model the human auditory system. The primate order possesses unique cortical specializations that govern auditory processing. Given the power of molecular and genetic tools available in the mouse model, it is essential to understand the similarities and differences in auditory cortical processing between mice and primates. To address this issue, we directly compared temporal encoding properties of neurons in the auditory cortex of awake mice and awake squirrel monkeys (SQMs). Stimuli were drawn from a sinusoidal amplitude modulation (SAM) paradigm, which has been used previously both to characterize temporal precision and to model the envelopes of natural sounds. Neural responses were analyzed with linear template-based decoders. In both species, spike timing information supported better modulation frequency discrimination than rate information, and multiunit responses generally supported more accurate discrimination than single-unit responses from the same site. However, cortical responses in SQMs supported better discrimination overall, reflecting superior temporal precision and greater rate modulation relative to the spontaneous baseline and suggesting that spiking activity in mouse cortex was less strictly regimented by incoming acoustic information. The quantitative differences we observed between SQM and mouse cortex support the idea that SQMs offer advantages for modeling precise responses to fast envelope dynamics relevant to human auditory processing. Nevertheless, our results indicate that cortical temporal processing is qualitatively similar in mice and SQMs and thus recommend the mouse model for mechanistic questions, such as development and circuit function, where its substantial methodological advantages can be exploited. NEW & NOTEWORTHY To understand the advantages of different model organisms, it is necessary to directly compare sensory responses across species. Contrasting temporal processing in auditory cortex of awake squirrel monkeys and mice, with parametrically matched amplitude-modulated tone stimuli, reveals a similar role of timing information in stimulus encoding. However, disparities in response precision and strength suggest that anatomical and biophysical differences between squirrel monkeys and mice produce quantitative but not qualitative differences in processing strategy.